Case Report: Roxadustat in Combination With Rituximab Was Used to Treat EPO-Induced Pure Red Cell Aplasia - You, Xiaoe; Guo, Baochun; Wang, Zhen; Ma, Hualin; Zhou, Ru; Liu, Lixia; Zhang, Xinzhou (Frontiers in Nephrology, 2022)
Recombinant human erythropoietin (rHuEPO) is a drug given to patients who have low hemoglobin related to chronic kidney disease or other anemia-related diseases. Some patients who receive rHuEPO repeatedly develop anti-rHuEPO neutralizing antibodies, leading to the occurrence of pure red cell aplasia (PRCA). PRCA associated with rHuEPO includes severe rHuEPO resistance, blood transfusion dependence, high serum ferritin, severe reticulocytopenia, and presence of anti-rHuEPO antibody. However, the optimal treatment of EPO-induced PRCA is unclear, therapeutic options against it remain a major clinical challenge. Herein, we report on 2 male patients with PRCA during rHuEPO treatment, who received combination therapy of roxadustat plus rituximab but had completely different clinical outcomes. The results obtained in this study show that roxadustat in combination with rituximab could be one of the treatment options for EPO-induced PRCA, but the treatment efficacy can vary from one individual to another. Additionally, we recommend starting reticulocytes monitoring and immunosuppressive agent therapy as early as possible to shorten the course of the disease and improve the outcomes of patients.